Training-level induced changes in blood parameters response to on-water rowing races - Desgorces, F. D.; Testa, M.; Petibois, C. (Journal of Sports Science & Medicine, 2008)
The study investigated blood markers allowing discriminating physiological responses to on-water rowing races, notably regarding training volume of athletes and race duration. College (COL) and national (NAT) rowers performed a 1000- or 2000-m race. Capillary blood samples obtained before and post-race allowed an analysis of a wide range of serum parameters. COL rowers had a lower rowing experience and training volume than NAT. Races induced a higher lactate concentration increase in NAT compared to COL (10.45 ± 0.45 vs 13.05 ± 0.60; p < 0.001). Race distance (2000 vs. 1000 m) induced a higher increase in fatty acids (0.81 ± 0.31 vs +0.67 ± 0. 41; p < 0.05) and triglycerides concentration in NAT (0.33 ± 0.07 vs 0.15 ± 0.09; p < 0.01), but remained comparable between NAT and COL for the 1000-m races. Amino acids concentrations increased in NAT (0.19 ± 0.03, p < 0.01), but urea concentration increased only for NAT rowers having performed the 2000-m race (0.72 ± 0.22, p < 0.05). Transferrin concentration decreased after the 2000-m race (-0.60 ± 0.25, p < 0.05), and concentration changes of haptoglobin differed between NAT2000 (tendency to be reduced) and COL (tendency to by enhanced) (p < 0.05). Our results confirmed that the training level in rowing is associated with higher glycolysis utilization during maximal 1000- and 2000-m exercise and no difference for similarly trained subjects at these two distances. Our study also demonstrated that a 2000-m race could initiate fatty and amino-acid metabolisms in highly trained subjects. Therefore, these changes in blood parameter responses to a characteristic rowing exercise highlighted the importance of monitoring the physiological effects of training in sporting conditions and according to individual characteristics.